2014
DOI: 10.1103/physrevlett.113.157203
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic Rhodium Clusters

Abstract: Simultaneous magnetic and electric deflection measurements of rhodium clusters (Rh(N), 6 ≤ N ≤ 40) reveal ferromagnetism and ferroelectricity at low temperatures, while neither property exists in the bulk metal. Temperature-independent magnetic moments (up to 1 μ(B) per atom) are observed, and superparamagnetic blocking temperatures up to 20 K. Ferroelectric dipole moments on the order of 1D with transition temperatures up to 30 K are observed. Ferromagnetism and ferroelectricity coexist in rhodium clusters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…In a previous study, Jinlong and coworkers [48] revealed that the lowest-energy geometry of Rh 12 is the distorted icosahedron (Rh-12-D). However, our findings indicate that Rh-12-D in both triplet and quintet state is quite unstable being 57.1 and 57.9 kcal/mol above the most stable structure Rh-12-A (D 4h , 9 A 1g ) which can be viewed as a double cube. The same structure Rh-12-A also found for various multiplicites namely triplet, septet, and 11tet are higher in energy.…”
Section: Rh-5-mentioning
confidence: 72%
See 2 more Smart Citations
“…In a previous study, Jinlong and coworkers [48] revealed that the lowest-energy geometry of Rh 12 is the distorted icosahedron (Rh-12-D). However, our findings indicate that Rh-12-D in both triplet and quintet state is quite unstable being 57.1 and 57.9 kcal/mol above the most stable structure Rh-12-A (D 4h , 9 A 1g ) which can be viewed as a double cube. The same structure Rh-12-A also found for various multiplicites namely triplet, septet, and 11tet are higher in energy.…”
Section: Rh-5-mentioning
confidence: 72%
“…The last isomer is a capped cube structure Rh-9-E (C 4v ) lying 11.4 kcal/mol higher in energy than the ground state Rh-9-A. It is interesting that several quasi-degenerate states compete for the ground state of Rh 9 , that is, the Rh-9-A with 15 A and 17 A and the Rh-9-B (C 1 , 15 A). The relative energies of other electronic states are listed in Table 3.…”
Section: Rh-5-mentioning
confidence: 98%
See 1 more Smart Citation
“…This prerequisite can be met if an intense and linearly polarized laser pulse interacts with a solid and leads to the emission of electron bunches within a half cycle of an optical laser field. In particular, the investigation of such kind of laser created dense electron bunches is motivated by the search for a relativistic electron mirror upon which a second laser pulse could be reflected and then is upshifted in frequency due to the relativistic Doppler effect [11,12,[14][15][16][17]. The efficiency of the relativistic backscattering process is dependent on a high density and narrow spectral distribution of the electron layer.…”
mentioning
confidence: 99%
“…In Refs. [74,75,76], the authors employed the color glass condensate framework [77,78,79,80] to describe J/ψ hadroproduction for p T comparable to, or even smaller than, the J/ψ mass, where the short-distance process is sensitive to the proton structure at very small Bjorken x. Based on the long-distance matrix elements determined in Ref.…”
Section: Discussionmentioning
confidence: 99%